![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
计算:(1)(-20)+(+3)-(-5)-(-7);(2)(?34?79+512)×(?36);(3)?22×(?5)?6÷(?2)2×|?14|
计算:(1)(-20)+(+3)-(-5)-(-7);(2)(?34?79+512)×(?36);(3)?22×(?5)?6÷(?2)2×|?14|....
计算:(1)(-20)+(+3)-(-5)-(-7);(2)(?34?79+512)×(?36);(3)?22×(?5)?6÷(?2)2×|?14|.
展开
1个回答
展开全部
(1)原式=-20+3+5+7
=-5;
(2)原式=(-
)×(-36)-
×(-36)+
×(-36)
=27+28-15
=40;
(3)原式=-4×(-5)-6÷4×
=20-
×
=20-
=19
.
=-5;
(2)原式=(-
3 |
4 |
7 |
9 |
5 |
12 |
=27+28-15
=40;
(3)原式=-4×(-5)-6÷4×
1 |
4 |
=20-
3 |
2 |
1 |
4 |
=20-
3 |
8 |
=19
5 |
8 |
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询